Textural Characteristics of Resorcinol—Formaldehyde Resin and Temperature Behavior of Bound Water Affected by Co-Adsorbed Trifluoroacetic Acid or Pyridine in Weakly Polar Organic Media - Vladimir M. Gun'ko; Vladimir V. Turov; Viktor M. Bogatyrov; Jadwiga Skubiszewska-Zięba; Barbara Charmas (Adsorption Science & Technology)
Resorcinol–formaldehyde resin (RFR) was synthesized as a porous material characterized by specific surface area of 140 m 2 /g and pore volume of 0.59 cm 3 /g with major proportions of broad mesopores and macropores. The interfacial behavior of water at low (h = 0.05 g of water/gram of dry RFR) and high (h = 2 g/g) hydration degrees depends on temperature and pore size filled by unfrozen water because its freezing-point depression increases in narrower pores. When water is mixed with co-adsorbates, the effects of such co-adsorbates as non-polar, weakly polar and polar organics depend on the amounts and the pore sizes. Even at a low hydration degree (h = 0.05 g/g), a portion of water can be displaced from pores by organic co-adsorbates because water has a relatively weak interaction with the RFR surface.